Estado, trabajadores y empleo femenino en los orígenes de la industria en la España contemporánea - Juanjo Romero Marín (Mélanges de la Casa de Velázquez)
This article seeks to explain the differential treatment of female workers in 19th-century industry as a holdover from earlier traditions. In particular it seeks the causes of the double standards of the industrial labour market in the political economy of the absolute monarchy at the close of the 18th century and in the employment practices of craft unions in the early 19th century. After analysing the role of the Enlightenment State in the creation of an industrial labour market, it goes on to examine the part played by craft unions in defining the future role of women in manufacturing. While the monarchy used female labour in pursuit of the country’s industrial take-off, assigning it a subsidiary role, it was the craft unions that defined the characteristics of such work. Both institutions were responsible for setting the basic conditions for female labour and a disparate labour market in contemporary Spain.